Oil revolution anticolonial elites, sovereign rights, and the economic culture of decolonization - Dietrich, Christopher R. W. (Cambridge, United Kingdom Cambridge University Press, 2017)
Through innovative and expansive research, Oil Revolution analyzes the tensions faced and networks created by anti-colonial oil elites during the age of decolonization following World War II. This new community of elites stretched across Iran, Iraq, Saudi Arabia, Venezuela, Algeria, and Libya. First through their western educations and then in the United Nations, the Arab League, and the Organization of Petroleum Exporting Countries, these elites transformed the global oil industry. Their transnational work began in the early 1950s and culminated in the 1973-4 energy crisis and in the 1974 declaration of a New International Economic Order in the United Nations. Christopher R. W. Dietrich examines how these elites brokered and balanced their ambitions via access to oil, the most important natural resource of the modern era.-- Provided by Publisher.
Machine generated contents note: 1. One Periphery: The Creation of Sovereign Rights, 1949 -- 1955 -- 2. Past Concessions: The Arab League, Sovereign Rights, and OPEC, 1955 -- 1960 -- 3. Histories of Petroleum Colonization: Oil Elites and Sovereign Rights, 1960 -- 1967 -- 4. Rights and Failure: The 1967 Arab Oil Embargo -- 5. Nationalist Heroes: Imperial Withdrawal, the Cold War, and Oil Control, 1967 -- 1970 -- 6. A Turning Point of Our History: The Insurrectionists and Oil, 1970 -- 1971 -- 7. A Fact of Life: The Consolidation of Sovereign Rights, 1971 -- 1973 -- 8. The OPEC Syndrome: The Third World's Energy Crisis, 1973 -- 1975.
Keywords: Organization of Petroleum Exporting Countries -- 20th century; Petroleum industry and trade -- Political aspects -- Developing countries -- 20th century; Natural resources -- Political aspects -- Developing countries -- 20th century; Decolonization -- Developing countries -- 20th century; Developing countries -- Foreign relations